Short article: The effect of implementation of a treatment algorithm for infliximab on remission rates and drug costs in inflammatory bowel disease patients. Issue 2 (February 2017) - Taks, Margot; Pijls, Phillipe A.R.R.; Derijks, Luc J.J.; ten Broeke, Robert; Grouls, Rene J.; Curvers, Joyce; Gilissen, Lennard P.L.
Abstract : Introduction: The effective, but expensive, drug infliximab is used in patients with inflammatory bowel disease (IBD). Monitoring infliximab trough levels and anti-infliximab antibody (ATI) formation can lead to a more cost-effective use of infliximab therapy. The aim of our study was to investigate the effect of implementation of a treatment algorithm for infliximab in a single-centre IBD cohort, focussing on remission rates and drug costs. Methods: IBD patients aged 18 years or older treated with infliximab were asked to participate in this study. Remission rates were assessed using faecal calprotectin levels and a validated questionnaire. Infliximab trough levels and ATIs were determined at baseline and at the third infliximab infusion. According to the advice given by the treatment algorithm, infliximab dosage adjustments were performed at the second infliximab infusion. Results: Between January and December 2015 a total of 62 IBD patients in our centre were treated with infliximab, of whom 33 (53%) patients agreed to participate in this study. The number of patients in remission was 28 (85%) at baseline and there were 13 dose adaptations suggested by the treatment algorithm for the successive second infusion. Four patients possessed undetectable infliximab levels and positive ATI status at baseline. After the second infusion, there were 29 (88%) patients in remission at the third infusion. All of this resulted in an annual drug cost reduction of [Euro sign]47 026 (7.4%). Conclusion: Our developed treatment algorithm of infliximab led to optimization of infliximab therapy in IBD patients by increasing remission rates and reducing drug costs.